Analyzing the Interconnected Influence of Profitability and Capital Structure on Firm Value (A Case Study of State-Owned Companies in the Construction Sector TBK From 2016-2020) - Salsabila Muslifah Adinda Supyan; Arif Kuswanto (Institut Pemerintahan Dalam Negeri, 2023)
Abstract State-owned companies operating in the construction sector are known to incur substantial and accumulating debt. This is attributed to the use of the capital structure through debt loans or external funding, often from foreign parties with multi-year payment terms. Therefore, this study aimed to identify and comprehensively analyze the reciprocal relationship between profitability and the capital structure, examining its impact on firm value. The array is specifically focused on State-Owned Companies in the Construction Sector over the period from 2016 to 2020. A quantitative approach was adopted in the selected methodology, with financial data extracted from 40 reports. The data analysis used various methods, including the Granger Causality, t-test, and Determination Test. The results showed a significant impact of profitability on the capital structure, and vice versa while showing a substantial influence on firm value. Additionally, the capital structure significantly impacted firm value in State-Owned Companies in the Construction Sector from 2016 to 2020. Keywords: Profitability, Capital Structure, Firm Value. Abstrak Perusahaan BUMN sektor kontruksi terindikasi adanya utang yang besar dan menumpuk. Hal ini disebabkan perusahaan karya menggunakan struktur modalnya dari pinjaman hutang atau pendanaan dari pihak luar atau asing dengan Multi year payment. Penelitian ini bertujuan untuk mengetahui dan menganalisis hubungan timbal balik antara profitabilitas dan struktur modal serta dampaknya terhadap nilai perusahaan (Studi pada perusahaan BUMN Sektor Kontruksi Tahun 2016-2020). Metode yang digunakan adalah kuantitatif dengan menggunakan 40 data laporan keuangan dan Teknik Analisis data yang digunakan adalah Uji Kausalitas Granger, Uji t dan Uji Determinasi. Hasil penelitian menunjukan profitabilitas berpengaruh signifikan terhadap struktur modal pada perusahaan BUMN Sektor Kontruksi Tbk tahun 2016-2020, Struktur modal berpengaruh signifikan terhadap profitabilitas pada Perusahaan BUMN Sektor Kontruksi Tbk tahun 2016-2020, Profitabilitas berpengaruh signifikan terhadap nilai perusahaan pada Perusahaan BUMN Sektor Kontruksi Tbk tahun 2016-2020, Struktur modal berpengaruh signifikan terhadap nilai perusahaan pada Perusahaan BUMN Sektor Kontruksi Tbk tahun 2016-2020. Kata kunci: Profitabilitas; Struktur Modal; Nilai Perusahaan